불매운동 참여의도에 영향을 미치는 요인에 관한 연구: 분노의 매개효과와 온라인 및 SNS 뉴스이용의 조절효과를 중심으로 - 이장석(Jang-Suk Lee); 김예인(Ye-In Kim) (한국콘텐츠학회 논문지, 21(12), 2021)
The boycott of Japanese products triggered by Japan's economic retaliation has heated up the Republic of Korea. This study examined the factors affecting the boycott participation intention in 217 college students and ordinary people in their 20s and 30s. The results of the study showed that perceived egregiousness, self-efficacy, and subjective norm had a positive effect on boycott participation intention, and perceived egregiousness had an indirect effect on boycott participation intention through anger. In addition, these overall impacts were moderated by online and SNS news usage. This study is significant in providing academic and practical implications for understanding boycott phenomena by verifying various influencing factors on consumer boycott intentions and comprehensively reviewing the mediating effect of anger and the moderating effect of online and SNS news usage. 일본의 경제보복으로 촉발된 일본제품 불매운동이 대한민국을 뜨겁게 달궜으며, 그 열기가 아직도 가시지 않은 채 현재 진행 중이다. 특히 '공정'을 중요한 가치로 여기는 MZ세대의 적극적 참여가 이번 불매운동의 성공 요인으로 평가받고 있다. 본 연구는 20~30대의 수도권 소재의 대학생 및 일반인 217명을 대상으로 소비자 불매운동 참여의도에 영향을 미치는 요인들을 확인하였다. 연구 결과, 지각된 악의성과 자기효능감, 주관적 규범이 불매운동 참여의도에 정적인 영향을 미치는 것으로 나타났다. 지각된 악의성은 분노를 매개로 불매운동 참여의도에 정적인 영향을 미치고 있었으며, 이러한 전체적인 영향은 소비자들의 온라인 및 SNS 뉴스이용수준에 따라 달라지고 있음을 확인하였다. 본 연구는 소비자 불매운동 참여의도에 미치는 다양한 영향요인을 발견하고 분노라는 정서의 매개작용과 온라인 및 SNS 뉴스이용의 조절적 영향을 종합적으로 검토함으로써 불매운동 현상을 이해하는 데 학문적, 실천적 시사점을 제공하는 데 의의를 두고 있다.